2008
DOI: 10.1128/jvi.01353-08
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Rous Sarcoma Virus DNA: a CA Dinucleotide Is Not Required for Integration of the U3 End of Viral DNA

Abstract: The two ends of RSV linear DNA are independently inserted into host DNA by integrase in vivo. We previously showed that the range of U3 sequences that are acceptable substrates for integrase appeared to be greater than the range of acceptable U5 sequences in vivo. We have done additional experiments to determine which U3 sequences are good integrase substrates. On the U3 end, there does not appear to be a stringent requirement for the canonical CA, integrase can efficiently remove three nucleotides, and six nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The conserved CA/GT sequence located 2 bp from the DNA end (immediately 5Ј of the scissile phosphodiester bond) comprises an invariant feature of the terminal inverted repeats. Surprisingly, some studies have shown that even these conserved dinucleotide pairs are not absolutely essential for IN-mediated DNA processing in vitro (4) or integration in vivo (5,6). Others have demonstrated cross-recognition of heterologous LTRs by retroviral IN proteins (7), which is typically accounted for by limited sequence identity between the cognate and heterologous DNA tips.…”
mentioning
confidence: 99%
“…The conserved CA/GT sequence located 2 bp from the DNA end (immediately 5Ј of the scissile phosphodiester bond) comprises an invariant feature of the terminal inverted repeats. Surprisingly, some studies have shown that even these conserved dinucleotide pairs are not absolutely essential for IN-mediated DNA processing in vitro (4) or integration in vivo (5,6). Others have demonstrated cross-recognition of heterologous LTRs by retroviral IN proteins (7), which is typically accounted for by limited sequence identity between the cognate and heterologous DNA tips.…”
mentioning
confidence: 99%
“…However, as has already been discussed, it is possible to create conditions under which IN can insert only one end of the viral DNA. When this happens, host enzymes insert the second viral DNA end into the host genome with an efficiency that can be as high as 30 % of the rate at which a normal viral DNA end can be inserted by IN [ 12 ]. This produces what at first appears to be a complex array of host/virus DNA junctions, in which the viral DNA sequences are often (but not always) truncated.…”
Section: Discussionmentioning
confidence: 99%
“…It should be clear that this homologous recombination can take place on either side of the initial IN-mediated event. Thus the host-mediated insertion reaction can lead to a deletion in the flanking host DNA if it takes place on one side of the initial IN-mediated integration event; if it takes place on the other side, it will cause a duplication of the flanking host DNA, as was shown in experiments done using ASLV-based vectors [ 11 , 12 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations